CRH Affects the Phenotypic Expression of Sepsis-Associated Virulence Factors by Streptococcus pneumoniae Serotype 1 In vitro - Ngo Ndjom, Colette G.; Kantor, Lindsay V.; Jones, Harlan P. (Frontiers in Cellular and Infection Microbiology, 2017)
Sepsis is a life-threatening health condition caused by infectious pathogens of the respiratory tract, and accounts for 28%-50% of annual deaths in the US alone. Current treatment regimen advocates the use of corticosteroids as adjunct treatment with antibiotics, for their broad inhibitory effect on the activity and production of pro-inflammatory mediators. However, despite their use, corticosteroids have not proven to be able to reverse the death incidence among septic patients. We have previously demonstrated the potential for neuroendocrine factors to directly influence Streptococcus pneumoniae virulence, which may in turn mediate disease outcome leading to sepsis and septic shock. The current study investigated the role of Corticotropin-releasing hormone (CRH) in mediating key markers of pneumococcal virulence as important phenotypic determinants of sepsis and septic shock risks. In vitro cultures of serotype 1 pneumococcal strain with CRH promoted growth rate, increased capsule thickness and penicillin resistance, as well as induced pneumolysin gene expression. These results thus provide significant insights of CRH-pathogen interactions useful in understanding the underlying mechanisms of neuroendocrine factor’s role in the onset of community acquired pneumonias (CAP), sepsis and septic shock.